Advances in athlete tracking technology - Holthouse, S. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Athlete tracking is increasingly ubiquitous in elite sport. For most practitioners this involves using data from heart rate sensors, GPS or video based tracking for velocity and distance and increasingly some basic accelerometer derived parameters. However the questions that coaches want to answer from athlete tracking technology continue to evolve and become more sophisticated. This paper discusses some advances in software and hardware from Catapult Sports in Australia that are keeping pace with those emerging issues. They include a practical solution to ball tracking in team sports, and a method of using inertial sensors to better measure the non running part of an athletes activity.